Variability of Earth’s ionospheric outflow in response to the dynamic terrestrial exosphere - Lin, Mei-Yun; Cucho-Padin, Gonzalo; Oliveira, Pedro; Glocer, Alex; Rojas, Enrique (Frontiers in Astronomy and Space Sciences, 2024)
The most abundant neutral constituent in the exospheric region (i.e., beyond ≈ 500 km altitude) is the atomic hydrogen (H); however, its density distributions predicted by physics-based models have been challenged by satellite-based observations of its far ultraviolet emissions. This discrepancy may impact magnetospheric ions’ densities and velocities since numerous chemistry and ion-neutral coupling interactions rely sensitively on the underlying neutral hydrogen population. The Polar Wind Outflow Model a first-principled model for relevant ion species in the high-latitude ionosphere, is employed to investigate the role of neutral H on the ionospheric outflow. Specifically, variability in the outflow of ionospheric H+, He+, N+, and O+ as a response to systematic enhancement and depletion of H number densities were simulated. The altitude-dependent ion density and energy partition profiles vary with neutral H density, solar activities, and ion species. These findings suggest that the exosphere plays a crucial role in controlling the production and loss of ions through ionospheric chemistry, as well as the energy contributions by altering ion-neutral-electron collisions and the ambipolar electric field to the high-latitude ionospheric outflow. As a result, the escape rates of the ionospheric outflow are directly associated with exospheric distributions. This work potentially helps understand the dominant mechanisms of atmospheric escape, particularly during a hydrogen-rich early Earth’s and exoplanet’s atmosphere, which is known to play a significant role in understanding the evolution of Earth’s atmosphere.